POTENSI ANTIBAKTERI EKSTRAK JAHE (Zingiber officinale Roscoe) TERHADAP Porphyromonas gingivalis SECARA IN VITRO - Zulfan M. Alibasyah; Ridha Andayani; Ana Farhana (Journal of Syiah Kuala Dentistry Society, 2016)
AbstractChronic periodontitis is the most common periodontal disease occurs in people with prevalence of96.58% and usually occurs at the age of 35 years and over. The main cause of chronic periodontitis isaccumulation of plaque and bacteria. The most dominant bacteria in chronic periodontitis isPorphyromonas gingivalis. Ginger (Zingiber officinale Roscoe) is a spice plant that is widely used bythe public, contain secondary metabolites such as flavonoids, terpenoids, phenols, and essential oilwhich is antibacterial. This study aim was to determined the gingers extract (Zingiber officinaleRoscoe) antibacterial potency against Porphyoromonas gingivalis with various concentrations are6.25%, 12.5%, 25%, 50%, and 100%. Antibacterial potency which test done by placing a paper discsthat has been dipped in the test group with 5 concentration and the placed on the surface of the MHAmedium (Mueller Hilton Agar) which had been grown Porphyromonas gingivalis, and incubated for 24hours at a temperature of 37 0C in an anaerobic atmosphere. Furthermore, inhibition zones werecalculated using calipers. Data were analyzed by one way ANOVA test which showed that the extractof ginger (Zingiber officinale Roscoe) can inhibit Porphyromonas gingivalis with probability (P0.05).Conclusion the extract of ginger (Zingiber officinale Roscoe) cold inhibit the growth ofPorphyromonas gingivalis at 6,25% concentration of extract with average of inhibition zone 10,6 mmthat categorized weak.Keywords: Ginger, Porphyromonas gingivalis, Chronic Periodontitis